Bullying behaviors and pro-social skills in peruvian adolescents aged 12 to 14 - Rosario Quiroz, Fernando Joel (2021)
Unesco (2018) indicates that one in three students are victims of bullying at school age, which is why the present research aimed to establish the link between pro-social ability and behaviors against bullying in Peruvian adolescents between 12 and 14 years old. The research was descriptive correlational type; the study sample consisted of 109 students calculated with the G * Power program version 3.1.9.4; the sampling used was non-probabilistic for convenience. The instruments used were piloted with a sample of 100 subjects, the scale of pro-social skills in adolescents (EHP-A) obtained a O = 0.943; and the Multimodal School Interaction Questionnaire (CMIE-IV) obtained O = 0.850. The results showed significant and inverse correlations with low effect sizes between pro-social skills and behaviors in the face of bullying, only direct and significant correlations were found between perspective taking, solidarity and response of help and altruism with active observer behavior in defense of the harassed. It is concluded that pro-social skills inversely explain behaviors in the face of bullying (X2 / gl = 1.877; GFI = .908; CFI = .915; IFI = .918; RMSEA = .090; SRMR = .0769).